Fibroblast-derived matrix models desmoplastic properties and forms a prognostic signature in cancer progression - Rafaeva, Maria; Jensen, Adina R. D.; Horton, Edward R.; Zornhagen, Kamilla W.; Strøbech, Jan E.; Fleischhauer, Lutz; Mayorca-Guiliani, Alejandro E.; Nielsen, Sebastian R.; Grønseth, Dina S.; Kuś, Filip; Schoof, Erwin M.; Arnes, Luis; et al. (Frontiers in Immunology, 2023)
The desmoplastic reaction observed in many cancers is a hallmark of disease progression and prognosis, particularly in breast and pancreatic cancer. Stromal-derived extracellular matrix (ECM) is significantly altered in desmoplasia, and as such plays a critical role in driving cancer progression. Using fibroblast-derived matrices (FDMs), we show that cancer cells have increased growth on cancer-associated FDMs, comparing to FDMs derived from non-malignant tissue (normal) fibroblasts. We assess the changes in ECM characteristics from normal to cancer-associated stroma at the primary tumor site. Compositional, structural, and mechanical analyses reveal significant differences, with an increase in abundance of core ECM proteins, coupled with an increase in stiffness and density in cancer-associated FDMs. From compositional changes of FDM we derived a 36-ECM proteins’ signature, which we show largely matching the changes in pancreatic ductal adenocarcinoma (PDAC) tumor and metastases progression, as well as at the transcriptomic level in multiple cancer types in patients, prognostic of their survival. Together, our results show relevance of FDMs for cancer modelling and identification of desmoplastic ECM components for further mechanistic studies.